The principles of project management - Williams, Meri.; Safari eBooks (Collingwood, Vic. : SitePoint ; Farnham : O'Reilly [distributor], 2008)
Presents information on principles that can be used in planning, managing, and leading business projects.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Project management; Electronic books